Mycoplasma pneumoniae Protein P30 Is Required for Cytadherence and Associated with Proper Cell Development - Romero-Arroyo, Cynthia E. (American Society for Microbiology, 1999)
The attachment organelle of Mycoplasma pneumoniae is a polar, tapered cell extension containing an intracytoplasmic, electron-dense core. This terminal structure is the leading end in gliding motility, and its duplication is thought to precede cell division, raising the possibility that mutations affecting cytadherence also confer a defect in motility or cell development. Mycoplasma surface protein P30 is associated with the attachment organelle, and P30 mutants II-3 and II-7 do not cytadhere. In this study, the recombinant wild-type but not the mutant II-3 p30 allele restored cytadherence when transformed into P30 mutants by recombinant transposon delivery. The mutations associated with loss of P30 in mutant II-3 and reacquisition of P30 in cytadhering revertants thereof were identified by nucleotide sequencing of the p30 gene. Morphological abnormalities that included ovoid or multilobed cells having a poorly defined tip structure were associated with loss of P30. Digital image analysis confirmed quantitatively the morphological differences noted visually. Transformation of the P30 mutants with the wild-type p30 allele restored a normal morphology, as determined both visually and by digital image analysis, suggesting that P30 plays a role in mycoplasma cell development. Finally, the P30 mutants localized the adhesin protein P1 to the terminal organelle, indicating that P30 is not involved in P1 trafficking but may be required for its receptor-binding function.